Differences in Efficacy Between Gamithromycin, Tilmicosin, and Tulathromycin as Metaphylactic Treatments in High Risk Calves for Bovine Respiratory Disease - T. Miller; M. E. Hubbert; E. F. Schwandt; D. U. Thomson; C. D. Reinhardt (Kansas Agricultural Experiment Station Research Reports, 2017)
The cost of Bovine Respiratory Disease to the beef industry due to death, poorer conversions, and therapy is estimated to cost more than $3 billion per year. Identifying and mitigating Bovine Respiratory Disease in cattle can be difficult due to the increased susceptibility for Bovine Respiratory Disease in high risk cattle. One management option to minimize an outbreak of respiratory disease is the use of metaphylaxis, the mass treatment of a group of calves to reduce the incidence and adverse effects of respiratory disease on high risk animals. Criteria used to determine the necessity of metaphylactic treatment against Bovine Respiratory Disease in feedlots can be based on several factors depending on feedlot preference; however, the primary criteria often considered are: a known history of no previous vaccinations, overall appearance of cattle, source of cattle, Bovine Respiratory Disease in calves received from same source previously, long shipping distance, season of the year, and light arrival weight. The objective of this study was to compare the efficacy of treating newly received, highrisk feedlot calves with gamithromycin, tulathromycin, and tilmicosin as metaphylactic treatments on health and performance characteristics.
Keywords: bovine respiratory disease; cattle; metaphylactic treatment